2020
DOI: 10.1111/jcpt.13313
|View full text |Cite
|
Sign up to set email alerts
|

Acarbose bioequivalence: Exploration of eligible protocol design

Abstract: What is known and objective Acarbose is a poorly absorbed α‐glucosidase inhibitor that acts locally in the intestinal tract. Therefore, the evaluation of its bioequivalence (BE) should be based on pharmacodynamic (PD) rather than pharmacokinetic (PK) endpoints. Currently, there is no consensus on the best method for acarbose BE evaluation. The optimal protocol design regarding dosing time/dose and PD parameters requires further exploration. The aim of the study was to identify an optimum protocol for establish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 9 publications
4
10
0
Order By: Relevance
“…The 90% confidence intervals of the geometric mean ratios of all the secondary endpoints, including baseline-corrected AUC 0-4h , r , the measured value method (C max , AUC 0-2h , AUC 0-4h ) and the measured value method of insulin level (ISLC max and ISLAUC 0-4h ) between the T and R drug were within the range of 80.00%-125.00%. The data in this pivotal study were consistent with that in the pilot study we previously reported [7] . The results in our pivotal study revealed that the new baseline-corrected PD endpoints were practical for discriminating the differences between preparations.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The 90% confidence intervals of the geometric mean ratios of all the secondary endpoints, including baseline-corrected AUC 0-4h , r , the measured value method (C max , AUC 0-2h , AUC 0-4h ) and the measured value method of insulin level (ISLC max and ISLAUC 0-4h ) between the T and R drug were within the range of 80.00%-125.00%. The data in this pivotal study were consistent with that in the pilot study we previously reported [7] . The results in our pivotal study revealed that the new baseline-corrected PD endpoints were practical for discriminating the differences between preparations.…”
Section: Discussionsupporting
confidence: 91%
“…Eligible subjects were selected from healthy Chinese volunteers (including males and females). Inclusion and exclusion criteria were described as previous studies [7] .…”
Section: Subjectsmentioning
confidence: 99%
See 2 more Smart Citations
“…Berberine may exert an antihyperglycemic action in the digestive tract prior to absorption because of its poor gut wall absorption and low bioavailability. It is similar to acarbose, an antihyperglycemic drug with low bioavailability due to poor absorption, and its therapeutic activity is within the gastrointestinal tract [ 351 ].…”
Section: Antidiabetic Activity Of Berberinementioning
confidence: 99%